Sunday
March 26, 2017

Post a New Question

Posted by on .

log_5[log_4(log_3(x))] = 1

log_5 = log with the base of 5
log_4 = log with the base of 4
log_3 = log with the base of 3


Answer: 3^1024


Too many logs in one equation. . .I don't know how to solve it

  • Math - Logarithmic - ,

    5^log_5[log_4(log_3(x))] = [log_4(log_3(x))] =5^1
    4^log_4(log_3(x))= (log_3(x))=4^5 = 1024
    3^log_3(x) =x =3^1024

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question